Implementation of Kahoot! to Full Lesson for X Grade High School Students - Adhitama , Muhammad Julian; Nadia, Hafizhatu; Rafidiyah, Dina (Eduinfo Media, 2022)
Learning English, specifically reading comprehension, required improvement since, during COVID-19, students only received reading assignments. Most high school teachers taught students strategies on how to read the text instead of text reading itself. This is why teachers should choose a better way of teaching reading comprehension, such as using Kahoot!. This paper attempted to integrate Kahoot! into reading comprehension lessons and investigate teacher and students’ responses to the lessons. This research utilized case-study, using descriptive and thematic analysis models. The subjects of this study were an English teacher and 105 grade X high school students. The researcher concluded that Kahoot! The lesson’s framework created for this research is useable, the teacher will use it later, and the students will be motivated to learn English with Kahoot! in class.